The Effect of Cost Leadership Strategy and Differentiation on Company Performance in the Silk Cloth Industry, Wajo Kampoeng BNI District - Masrullah, Masrullah; Adziem, Faidul; Nasrun, Muhammad; Yanti, Reski (Invoice : Jurnal Ilmu Akuntansi, 2023)
This study aims to investigate the influence of cost leadership and differentiation strategies on the performance of companies operating in the silk fabric industry in Wajo Kampoeng district, BNI. The research adopts a quantitative approach. The study population consists of all employees within the silk fabric industry in Wajo Kampoeng Regency, BNI. Primary data was collected through the distribution of questionnaires to 30 respondents. The research instrument utilized the Likert Scales method, and data analysis was conducted using the Social Science Application Statistics Packages (SPSS) version 25. The research findings indicate that (1) the variable representing the cost leadership strategy has a significantly positive impact on company performance, and (2) the differentiation strategy variable also significantly influences company performance. Based on these results, it can be concluded that both cost leadership and differentiation strategies play crucial roles in enhancing company performance within the silk fabric industry. These findings provide valuable insights for businesses in this sector, highlighting the importance of strategic management in achieving and sustaining competitiveness and success.